2011
DOI: 10.21446/scg_ufrj.v6i1.13231
|View full text |Cite
|
Sign up to set email alerts
|

Uma Análise Da Terceirização Em Hospitais Localizados na Região Metropolitana De Belo Horizonte

Abstract: Têm surgido nos últimos anos algumas iniciativas voltadas tanto para a redução dos custos em hospitais como para a profissionalização e aperfeiçoamento da gestão dessas organizações. Dentre essas iniciativas, está a terceirização - transferência para terceiros de parte das atividades de uma empresa –, que vem sendo empregada pelos hospitais como uma estratégia de gestão e que se configura como uma opção de modernização e posicionamento competitivo ante as necessidades do mercado com relação aos custos e à qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Some studies such as that by Souza et al () showed outsourcing as an initiative used by hospitals to reduce costs and professionalize and improve the management of these sectors, as an option for innovative and competitive positioning with respect to costs and quality of services provided.…”
Section: Propositionsmentioning
confidence: 99%
“…Some studies such as that by Souza et al () showed outsourcing as an initiative used by hospitals to reduce costs and professionalize and improve the management of these sectors, as an option for innovative and competitive positioning with respect to costs and quality of services provided.…”
Section: Propositionsmentioning
confidence: 99%
“…For Brazilian publications, the keywords were considered in both languages to include all the possibilities and then removed from the final sample if it didn't fit the research objectives. We chose to use the keyword 'outsourcing' instead of 'externalisation' because the word has a broader meaning (SOUZA; BACIC, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Considerada uma atividade meio, em razão do efeito da alimentação na terapêutica em hospitais geridos pela Administração Pública, geralmente a UAN é uma das principais áreas em que ocorre a terceirização (Souza, Lara, Lima & Xavier, 2011).…”
Section: Introductionunclassified